2020
DOI: 10.17582/journal.jis/2020/6.1.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Toxic and Repellent Characteristics of Some Plant Extracts used against Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) Improve the Grain Quality of Stored Wheat

Abstract: Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) is one of the key insect pests of stored grains. Due to export regulations and zero-tolerance for alive insects in trade commodities, synthetic pesticides are often used to eliminate pest infestation in consignments. Phosphine is currently one and the only acceptable chemical used in stored grains, but due to their overuse, stored grain pests become resistant to this fumigant. There is, therefore, a great need to find alternatives. In this study insectic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The main effects and interaction of various crude plant extracts and their doses are highly significant (P < 0.05) on percent mortality of T. castaneum at two different exposure intervals. The highest and lowest percent mortality (55.83±2.17% and 29.17±1.65%) was recorded in Z. officinale and A. indica treated wheat after 10 DEI, respectively, while no mortality was recorded in control treatment at both exposure intervals [15]. [16] observed that neem controlled up to 45.63% red flour beetle population after 168 h interval.…”
Section: B Percentage Mortalitymentioning
confidence: 99%
“…The main effects and interaction of various crude plant extracts and their doses are highly significant (P < 0.05) on percent mortality of T. castaneum at two different exposure intervals. The highest and lowest percent mortality (55.83±2.17% and 29.17±1.65%) was recorded in Z. officinale and A. indica treated wheat after 10 DEI, respectively, while no mortality was recorded in control treatment at both exposure intervals [15]. [16] observed that neem controlled up to 45.63% red flour beetle population after 168 h interval.…”
Section: B Percentage Mortalitymentioning
confidence: 99%